Focus on transparency, strategic planning to effectively manage challenges resulting from pandemic - McCarthy, Claudine (College Athletics and the Law, 2020)
Transparency and strategic planning will play critical roles in leading athletics departments through the uncertain and unusual times surrounding the COVID‐19 crisis. That's according to Jacque Bruns, M.B.A., Senior Associate Athletics Director and Chief Financial Officer at Oregon State University; and Jonathan Butros, M.B.A., Senior Associate AD and Chief Financial Officer at Texas Tech University, who shared their views during a virtual forum hosted by Tom McMillen, President and Chief Executive Officer of the LEAD1 Association.